2001
DOI: 10.1162/003355301753265624
|View full text |Cite
|
Sign up to set email alerts
|

Skill-Biased Organizational Change? Evidence from A Panel of British and French Establishments

Abstract: This paper investigates the determination and consequences of organizational changes (OC) in a panel of British and French establishments. Organizational changes include the decentralization of authority, delayering of managerial functions, and increased multitasking. We argue that OC and skills are complements. We offer support for the hypothesis of "skill-biased" organizational change with three empirical findings. First, organizational changes reduce the demand for unskilled workers in both countries. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
575
4
32

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 804 publications
(640 citation statements)
references
References 37 publications
29
575
4
32
Order By: Relevance
“…In a sample of British firms (Nickell and Van Reenen, 2000), and of British and French firms (Caroli and Van Reenen, 2001), the link between workplace innovation and firm productivity was found to be more apparent when labour relations systems developed joint practices for firms and workers to be involved in decision-making and problem-solving. Another set of studies conducted on British firms (Bloom et al, 2005;Clayton, Sadun and Farooqui, 2007) found that ICT investment and use have a significant impact on firm productivity, albeit to varying degrees.…”
Section: Ict Innovation and Firms Labour Productivity: A Review Frommentioning
confidence: 99%
“…In a sample of British firms (Nickell and Van Reenen, 2000), and of British and French firms (Caroli and Van Reenen, 2001), the link between workplace innovation and firm productivity was found to be more apparent when labour relations systems developed joint practices for firms and workers to be involved in decision-making and problem-solving. Another set of studies conducted on British firms (Bloom et al, 2005;Clayton, Sadun and Farooqui, 2007) found that ICT investment and use have a significant impact on firm productivity, albeit to varying degrees.…”
Section: Ict Innovation and Firms Labour Productivity: A Review Frommentioning
confidence: 99%
“…Skilled workers are more able to better able to communicate information, they have a relative a d v antage in multi-tasking, and the costs of training them is lower compared to unskilled workers. Hence, the returns to innovative work practices could beexpected to be higher when the skill level of the workforce in an establishment is higher (Caroli and van Reenen, 2001). Similar to the case of a skill-biased technological change, one would expect a relative increase in the employment of skilled workers and professionals and engineers.…”
Section: Econometric Speci Cationmentioning
confidence: 99%
“…First, Z et and I et are likely to be endogenous (Caroli andvan Reenen, 2001 Athey andStern, 1998). A positive demand shock, for example, might enable rms to increase the number of skilled workers, to invest in new technologies, and to experiment with innovative w orkplace systems.…”
Section: Econometric Speci Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, effects are consistent across urban versus rural locations and across high versus low knowledge intensive sectors. Analysis of panel data from for British and French firms (Caroli and Van Reenen, 2001) revealed that skilled workers adapt more easily to changes in organization. Having the above in mind, the authors presented empirical evidence of relationship between workplace innovation and human capital, and its influence on productivity.…”
Section: Literature Review: Ict Innovation and Firm Productivitymentioning
confidence: 99%